2015
DOI: 10.1111/aji.12431
|View full text |Cite
|
Sign up to set email alerts
|

Immunocontraception for Animals: Current Status and Future Perspective

Abstract: An alternative to surgical sterilization for fertility control of animals (wild, zoo, farm, and domestic) is needed to prevent problems related to overpopulation, including culling and relocation. A PubMed and Google Scholar database search was conducted using the keywords 'contraceptive vaccine animals,' 'immunocontraception animals,' 'non-surgical sterilization animals,' 'PZP vaccine,' and 'GnRH vaccine.' The searches from 1972 to 2015 yielded over 1500 publications. These articles were read, and 375 were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 114 publications
(151 reference statements)
0
29
0
3
Order By: Relevance
“…; Jurdak et al . ; Naz & Saver ). It is therefore foreseeable that applications of current technology, let alone new technology, will reduce the cost of control, increase effectiveness and further reduce animal suffering if governments choose to invest in this area.…”
Section: Animal Welfare and The Ethics Of Aerial Cullingmentioning
confidence: 99%
See 1 more Smart Citation
“…; Jurdak et al . ; Naz & Saver ). It is therefore foreseeable that applications of current technology, let alone new technology, will reduce the cost of control, increase effectiveness and further reduce animal suffering if governments choose to invest in this area.…”
Section: Animal Welfare and The Ethics Of Aerial Cullingmentioning
confidence: 99%
“…Ongoing control is a very standard practice and is why the Australian Capital Territory has remained largely feral horse free (ACT Government 2007). The nature of pest species control is undergoing a technological revolution at the moment (Campbell et al 2015;Jurdak et al 2015;Naz & Saver 2016). It is therefore foreseeable that applications of current technology, let alone new technology, will reduce the cost of control, increase effectiveness and further reduce animal suffering if governments choose to invest in this area.…”
Section: Animal Welfare and The Ethics Of Aerial Cullingmentioning
confidence: 99%
“…Immunocastration or vaccination against the GnRH‐I hormone produces an immunological barrier between the hypothalamus and the anterior hypophysis, modifying gonadal function and sexual behavior . This is a promising alternative to reproductive control and has been investigated in domestic, productive, and wild animals . Given the low immunogenicity of this hormone, it becomes necessary to increase the antigenic immune response using adjuvants …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sources of native CRISP1 protein limit its further application. Recombinant CRISP1 is relatively easy to obtain and had successfully produced a specific immune response, but it needs to be used in conjunction with the Freund's adjuvants, which are primarily related to the injection site reactions . As the first study on DNA vaccination based upon sperm antigens YLP12 and FA‐1 by Naz RK et al which showed exciting immunocontraceptive effects, several other sperm antigen‐based DNA vaccines have been investigated .…”
Section: Discussionmentioning
confidence: 99%